2019
DOI: 10.1093/bioinformatics/btz816
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of contact prediction: evidence that contact selection in statistical contact prediction is changing

Abstract: Motivation Over the last few years, the field of protein structure prediction has been transformed by increasingly-accurate contact prediction software. These methods are based on the detection of coevolutionary relationships between residues from multiple sequence alignments. However, despite speculation, there is little evidence of a link between contact prediction and the physico-chemical interactions which drive amino-acid coevolution. Furthermore, existing protocols predict only a fracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…(iv) McLachlan-based Substitution Correlation (McBASC [57][58][59] ), which is based on coordinated changes within physiochemical classes; and (v) Z-Normalized Mutual Information (ZNMI 52 ), which uses an information theoretic approach. Although several newer co-evolutionary analyses have been developed, the focus of the field has been on improving amino acid contact prediction (reviewed in 60 ). We decided not to use these versions: since many rheostat positions do not contact each other, we reasoned that these algorithms would impose unsuitable constraints.…”
Section: Bioinformatic Score Calculationsmentioning
confidence: 99%
“…(iv) McLachlan-based Substitution Correlation (McBASC [57][58][59] ), which is based on coordinated changes within physiochemical classes; and (v) Z-Normalized Mutual Information (ZNMI 52 ), which uses an information theoretic approach. Although several newer co-evolutionary analyses have been developed, the focus of the field has been on improving amino acid contact prediction (reviewed in 60 ). We decided not to use these versions: since many rheostat positions do not contact each other, we reasoned that these algorithms would impose unsuitable constraints.…”
Section: Bioinformatic Score Calculationsmentioning
confidence: 99%
“…Since no method has been shown to find more “important” positions than any other method, we previously used five, mathematically-divergent co-evolution algorithms for our studies (45, 46): (i) Observed Minus Expected Squared (OMES; (114, 115)), which is based on Chi-squared-like goodness of fit); (ii) Explicit Likelihood of Subset Covariation (ELSC; (116)) and (iii) Statistical Coupling Analysis (SCA; (117)), which are based on a subset perturbation approach; (iv) McLachlan-based Substitution Correlation (McBASC; (118-120)), which is based on coordinated changes within physiochemical classes; and (v) Z-Normalized Mutual Information (ZNMI; (113)), which uses an information theoretic approach. Although several newer co-evolutionary analyses have been developed, the focus of the field has been on improving amino acid contact prediction (reviewed in (121)). We decided not to use these versions because, since many rheostat positions do not contact each other, we reasoned that these algorithms would impose unsuitable constraints.…”
Section: Methodsmentioning
confidence: 99%
“…These interactions are prone to fracture due to external forces (e.g., heat), resulting in protein deactivation. Previous studies [45,46] have suggested that evolutionary couplings can detect side-chain interactions.…”
Section: Prediction Performance Of Physical-chemical Interactionmentioning
confidence: 99%